Green Human Resource Practices on Pro-environmental behaviour of workers: Case of Pakistani construction industry - Maqsoom, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Workers are a true asset of the construction industry, however, due to the less attention given by industry pro-environmental behaviour of workers got affected. Therefore, the persistence of this study is to investigate the variables that affect the pro-environmental behaviour of workers in construction industry. In this regard, a questionnaire was developed comprised of questions that were correlated with pro-environmental behaviour and was distributed among the stakeholders of the Pakistani construction industry. Upon receiving the feedback and making the statistical assessment, it was revealed that among these cognitive variables, environmental awareness related variables are primarily impacting the pro-environmental behaviour, followed by green management-related variables and responsible leadership related variables. Whereas green shared vision-related variables are relatively less important. The investigations of the present study give practical ramifications to organizations' top supervisors to create compelling devices and persuade their subordinates to actualize environmental practices. Â© 2021 IEEE.